Solid-state nanopore analysis on the conformation change of DNA polymerase I induced by a DNA substrate. Issue 13 (9th June 2022) - Fu, Jiye; Wu, Linlin; Hu, Gang; Li, Fuyao; Ge, Qinyu; Lu, Zuhong; Tu, Jing
Abstract : We studied the conformational changes between a Klenow fragment and its monomer complex with a DNA substrate using a SiN nanopore and found that the monomer complex has a tighter structure and transports slower. Abstract : Proteins with a changeable conformation, such as polymerases, play a very important role in various life activities. Their conformational changes can be reflected in their structural size and flexibility, which may influence their transport kinetics. Recently, solid-state nanopore sensors have been widely applied to characterize the conformation of proteins and other complex structures as sensitive and high throughput single-molecule detectors. In this work, we used a SiN nanopore sensor to study the conformational changes between the Klenow fragment (KF) and its monomer complex with a DNA substrate (KF-DNA). By calculating their hydrodynamic radii, pore volume, the duration of translocation events, drift velocity, and molecular dynamics simulations, we found that the KF-DNA monomer complex has a tighter structure and transports slower. The study performed here can be potentially used to identify single polymerases in real time and may ultimately reveal conformation changes and the interaction between polymerases and their substrates.